Helicene synthesis by Brønsted acid-catalyzed cycloaromatization in HFIP [(CF3)2CHOH] - Fujita, Takeshi; Shoji, Noriaki; Yoshikawa, Nao; Ichikawa, Junji (Beilstein Journal of Organic Chemistry, 2021)
A facile synthesis of carbo- and heterohelicenes was achieved via tandem cycloaromatization of bisacetal precursors, which were readily prepared through C–C bond formation by Suzuki–Miyaura coupling. This cyclization was efficiently realized by a catalytic amount of trifluoromethanesulfonic acid (TfOH) in a cation-stabilizing solvent, 1,1,1,3,3,3-hexafluoropropan-2-ol (HFIP), which readily allowed gram-scale syntheses of higher-order helicenes, double helical helicenes, and heterohelicenes.
Keywords: acid; catalyst; cyclization; fluoroalcohol; helicenes

(untitled) - Shen, Y.; Chen, C.-F. (Chem. Rev., 2012)

(untitled) - Gingras, M. (Chem. Soc. Rev., 2013)

(untitled) - Gingras, M.; Félix, G.; Peresutti, R. (Chem. Soc. Rev., 2013)

(untitled) - Gingras, M. (Chem. Soc. Rev., 2013)

(untitled) - Li, C.; Yang, Y.; Miao, Q. (Chem. – Asian J., 2018)

(untitled) - Dhbaibi, K.; Favereau, L.; Crassous, J. (Chem. Rev., 2019)

(untitled) - Newman, M. S.; Lutz, W. B.; Lednicer, D. (J. Am. Chem. Soc., 1955)

(untitled) - Verbiest, T.; Van Elshocht, S.; Kauranen, M.; Hellemans, L.; Snauwaert, J.; Nuckolls, C.; Katz, T. J.; Persoons, A. (Science, 1998)

(untitled) - Verbiest, T.; Van Elshocht, S.; Persoons, A.; Nuckolls, C.; Phillips, K. E.; Katz, T. J. (Langmuir, 2001)

(untitled) - Clays, K.; Wostyn, K.; Persoons, A.; Maiorana, S.; Papagni, A.; Daul, C. A.; Weber, V. (Chem. Phys. Lett., 2003)

(untitled) - Zhao, W.-L.; Li, M.; Lu, H.-Y.; Chen, C.-F. (Chem. Commun., 2019)
and references cited therein.

(untitled) - Mallory, F. B.; Mallory, C. W. (Org. React., 1984)

(untitled) - Flammang-Barbieux, M.; Nasielski, J.; Martin, R. H. (Tetrahedron Lett., 1967)

(untitled) - Mori, K.; Murase, T.; Fujita, M. (Angew. Chem., Int. Ed., 2015)

(untitled) - Mandal, B. K.; Sooksimuang, T. (J. Porphyrins Phthalocyanines, 2002)

(untitled) - Harrowven, D. C.; Nunn, M. I. T.; Fenwick, D. R. (Tetrahedron Lett., 2002)

(untitled) - Collins, S. K.; Grandbois, A.; Vachon, M. P.; Côté, J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Teplý, F.; Stará, I. G.; Starý, I.; Kollárovič, A.; Šaman, D.; Rulíšek, L.; Fiedler, P. (J. Am. Chem. Soc., 2002)

(untitled) - Hosokawa, T.; Takahashi, Y.; Matsushima, T.; Watanabe, S.; Kikkawa, S.; Azumaya, I.; Tsurusaki, A.; Kamikawa, K. (J. Am. Chem. Soc., 2017)

(untitled) - Fujita, T.; Takahashi, I.; Hayashi, M.; Wang, J.; Fuchibe, K.; Ichikawa, J. (Eur. J. Org. Chem., 2017)

(untitled) - Takahashi, I.; Hayashi, M.; Fujita, T.; Ichikawa, J. (Chem. Lett., 2017)

(untitled) - Takahashi, I.; Fujita, T.; Shoji, N.; Ichikawa, J. (Chem. Commun., 2019)

(untitled) - Bégué, J.-P.; Bonnet-Delpon, D.; Crousse, B. (Synlett, 2004)

(untitled) - Shuklov, I. A.; Dubrovina, N. V.; Börner, A. (Synthesis, 2007)

(untitled) - Dohi, T.; Yamaoka, N.; Kita, Y. (Tetrahedron, 2010)

(untitled) - Khaksar, S. (J. Fluorine Chem., 2015)

(untitled) - Colomer, I.; Chamberlain, A. E. R.; Haughey, M. B.; Donohoe, T. J. (Nat. Rev. Chem., 2017)

(untitled) - Ichikawa, J.; Miyazaki, S.; Fujiwara, M.; Minami, T. (J. Org. Chem., 1995)

(untitled) - Bowles, D. M.; Anthony, J. E. (Org. Lett., 2000)

(untitled) - Komeyama, K.; Okamoto, Y.; Takaki, K. (Angew. Chem., Int. Ed., 2014)

(untitled) - Zhang, K.; Cai, L.; Jiang, X.; Garcia-Garibay, M. A.; Kwon, O. (J. Am. Chem. Soc., 2015)

(untitled) - Fuchibe, K.; Imaoka, H.; Ichikawa, J. (Chem. – Asian J., 2017)

(untitled) - Murai, M.; Ogita, T.; Takai, K. (Chem. Commun., 2019)